Interim report to the government of the Federation of Nigeria on advanced training in the building trades at the Government Trade Centre, Enugu (I.L.O., 1963)
International Labour Office. Expanded programme of technical assistance. ILO/TAP/Nigeria/R. 4. Stencil.